Presentations and outcomes among sickle cell disease patients with COVID-19 at a large southern healthcare system. Issue 2 (1st February 2023) - Clarke, Karen; Shin, Yoo Mee; Hall, Mary Ann Kirkconnell; Moussa, Mohamad; McLemore, Morgan; El Rassi, Fuad
ABSTRACT: Objectives: Compared with the general population, patients with sickle cell disease (SCD) typically have substantially reduced life expectancies. It is unclear whether SCD patients who acquire COVID-19 have higher rates of complications and mortality than the general population. We sought to elucidate COVID-19 presentation and outcomes in patients with SCD. Methods: Using retrospective chart review, we evaluated demographic characteristics, presenting symptoms, chest imaging findings, blood transfusion requirements, need for mechanical ventilation or pressor support, medication administration (including remdesivir and dexamethasone), and survival among individuals with SCD hospitalized with COVID-19 from March 2020 to December 2021. Results: Among 72 SCD patients, increased pain was the most common presenting symptom followed by cough, fever, and dyspnea. Thirty-seven (44%) received simple transfusion and 14 (17%) underwent exchange transfusion. Lung imaging findings suggestive of COVID-19 were observed in 27 (37%) patients; 21 (29%) patients were treated with remdesivir and 26 (35%) received dexamethasone. Three patients (4%) required mechanical ventilation and pressor support; all three died from COVID complications. Conclusions: Pain is the most common presenting symptom in SCD patients with COVID-19. We observed a mortality rate higher than that among the general population among patients who required mechanical ventilation and pressor support.